If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + 9q = 29 Solving 7p + 9q = 29 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9q' to each side of the equation. 7p + 9q + -9q = 29 + -9q Combine like terms: 9q + -9q = 0 7p + 0 = 29 + -9q 7p = 29 + -9q Divide each side by '7'. p = 4.142857143 + -1.285714286q Simplifying p = 4.142857143 + -1.285714286q
| 8x-79=3x-9 | | Y=8x-79 | | -0.9156*d^3-0.1962*d^2+422.4163=0 | | 14-4x=-10 | | 6-5x=-59 | | 10x-8=7x+9 | | 13+7x=48 | | 7x+5=95 | | 8x-1=95 | | 13+8x=37 | | 3=6x-15 | | 6-5x=-54 | | 3y+8=8y-17 | | 6x(11+4)=-3 | | 3(10x-2)=8 | | 8x-5=123 | | 15-4x=-9 | | y^2-5y-20=0 | | 16-4x=-4 | | 6-5x=-49 | | 5x+14=-14-2x | | 5x+2y+9z-3x+5z-3y= | | 2+8x=122 | | X=8x-79 | | 9-8x=-111 | | 5x+3+2x-1=16 | | 16-5x=-4 | | 6+12x=-27+x | | 2-8x=54 | | 14x+6x=38 | | 13x+5x-5x= | | 6(x+3)=4(x-9) |